Frontal lobe syndrome reassessed: comparison of patients with lateral or medial frontal brain damage. Issue 5 (1st November 1999) - Paradiso, Sergio; Chemerinski, Eran; Yazici, Kazim M; Tartaro, Armando; Robinson, Robert G
Abstract : Examination of mood and behaviour changes after frontal damage may contribute to understanding the functional role of distinct prefrontal areas in depression and anxiety. Depression and anxiety disorders, symptoms, and behaviour were compared in eight patients with single lateral and eight patients with single medial frontal lesions matched for age, sex, race, education, socioeconomic status, side, and aetiology of lesion 2 weeks and 3 months after brain injury. DSM IV major depressive and generalised anxiety disorders were more frequent in patients with lateral compared with medial lesions at 2 weeks but not at 3 months. At 3 months, however, patients with lateral damage showed greater severity of depressive symptoms, and greater impairment in both activities of daily living and social functioning. At initial evaluation depressed mood and slowness were more frequent, whereas at 3 months slowness, lack of energy, and social unease were more frequent in the lateral than the medial group. Patients with lateral lesions showed greater reduction of emotion and motivation (apathy) during both examinations. Medial frontal injury may fail to produce emotional dysregulation or may inhibit experience of mood changes, anxiety, or apathy. Lateral prefrontal damage may disrupt mood regulation and drive while leaving intact the ability to experience (negative) emotions.